The Europeanisation of national administrations : patterns of institutional change and persistence - Knill, Christoph (Themes in European governance., 2001)
The Europeanisation of National Administrations analyzes the impact of European policies on national bureaucracies. Knill's study is a comparative assessment of the factors influencing administrative adjustment to European policy demands in the member states, and contains a detailed account of the administrative impact of European Union environmental policy in Britain and Germany. This book will interest students and scholars of European studies, comparative politics, environmental politics, public administration and organizational studies.